Do Taxes Crowd Out Intrinsic Motivation? Field-Experimental Evidence from Germany - Johannes Rincke; Pierre Boyer; Nadja Dwenger (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper studies how imposing norms on contribution behavior affects individuals' intrinsic motivation. We consider an urban area in Germany where the Catholic Church collects a local church levy as a charitable donation, despite the fact that the levy is legally a tax. In cooperation with the church, we design a natural randomized field experiment with letter treatments informing individuals that the church levy is in fact a tax. Guided by a simple theoretical model, we use baseline contribution behavior to measure individuals' intrinsic motivation and demonstrate that treatment effects differ strongly across motivational types. Among weakly intrinsically motivated individuals, communicating the existence of a legal norm results in a significant crowd-out of intrinsic motivation. In contrast, strongly intrinsically motivated individuals do not show any treatment response. We cross-validate our findings using alternative motivational measures derived from an extensive post-treatment survey.
Keywords: C93; D03; H26; 330